Risk Analysis in the Implementation of Phase II Development Project of the South Kalimantan Provincial Social Service Office - Noor, Athafa'iq Mufadhadal; Karim, Abdul (CERUCUK, 2025)
In its implementation, construction projects increase yearly due to the high demand for infrastructure such as buildings, roads, and bridges. These projects are not free from risks that can affect cost, time, and quality. This study focuses on the Phase II Development Project of the South Kalimantan Provincial Social Services Office to analyze potential risks. The research method employs a quantitative approach by analyzing Probability and Impact data using the Severity Index. The results are applied to the Probability and Impact Matrix to identify dominant risks and categorize them based on the risk acceptance scale. The findings reveal 12 valid risk variables, with 10 risks categorized as medium and 2 as high. The study provides risk response recommendations to mitigate impacts on the project. Keywords: Risk analysis, Severity Index, Probability and Impact Matrix, dominant risk variable.